2010
DOI: 10.1111/j.1741-3737.2009.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Stage in Young Adulthood and Intergenerational Congruence in Family Attitudes

Abstract: We investigated how intergenerational congruence in family-related attitudes depends on life course stage in young adulthood. Recent data from the Netherlands Kinship Panel Study were used; the present sample included 2,041 dyads of young adults and their parents. Findings are discussed in terms of the elasticity in intergenerational attitude congruence in response to young adults' life course transitions. Our results suggest that intergenerational congruence in attitudes about partnership (e.g., marriage, coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…For children therefore, parents form the main socializing agents (Glass, Bengtson, and Dunham 1986). Although not all attitudes are transmitted equally strongly from parents to children, gender ideologies have been found to be successfully transmitted from one generation to the next (Moen, Erickson, and Dempster-McClain 1997;Bucx, Raaijmakers, and van Wel 2010). Among minority populations, socialization practices serve the function of maintaining strong ethnic or religious group ties in the face of external pressures, and are therefore expected to be particularly strong in an immigration context (Bankston and Zhou 1997;Chong 1998).…”
Section: The Pivotal Role Of the Familymentioning
confidence: 99%
“…For children therefore, parents form the main socializing agents (Glass, Bengtson, and Dunham 1986). Although not all attitudes are transmitted equally strongly from parents to children, gender ideologies have been found to be successfully transmitted from one generation to the next (Moen, Erickson, and Dempster-McClain 1997;Bucx, Raaijmakers, and van Wel 2010). Among minority populations, socialization practices serve the function of maintaining strong ethnic or religious group ties in the face of external pressures, and are therefore expected to be particularly strong in an immigration context (Bankston and Zhou 1997;Chong 1998).…”
Section: The Pivotal Role Of the Familymentioning
confidence: 99%
“…The process of distancing enables the adult child to reflect on himself in the child role and to develop a realistic, more objective view on the relationship with the parent. The second dimension, comprehension, which may occur when the child enters the adult’s world of work and partner relations (Buhl 2007 ) or parenting (Bucx et al 2010 ), is described by Nydegger ( 1991 ) as a ‘gradual deepening’ of comprehending the parent. When the adult child is able to understand the parent’s world and the way life choices and opinions of the parent have been shaped, the final phase of this development is accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Although efficacy beliefs and permissive sexual attitudes are expected to be influential, individuals’ life experiences, including prior risky sexual experiences, likely have greater implications for behavior (e.g., Bucx, Raaijmakers, & van Wel, 2010). Studies focusing on high-risk populations have found positive associations between behavioral risks and HIV testing (e. g., Anderson, Carey & Taveras, 2000; Choi & Catania, 1996; Denison, Lungu, Dunnett-Dagg, McCauley, & Sweat, 2006; Stein & Nyamathi, 2000; Setia, Quesnel-Vallee, Curtis, & Lynch, 2009; Straub et al 2011; Tolou-Shams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%